Assessing trauma in a transcultural context: challenges in mental health care with immigrants and refugees - Lloy Wylie; Rita Van Meyel; Heather Harder; Javeed Sukhera; Cathy Luc; Hooman Ganjavi; Mohamad Elfakhani; Nancy Wardrop (Frontiers Media S.A., 2018)
Abstract The growing numbers of refugees and immigrants from conflict-prone areas settling throughout the world bring several challenges for those working in the mental health care system. Immigrants and refugees of all ages arrive with complex and nuanced mental health histories of war, torture, and strenuous migration journeys. Many of the challenges of addressing the health care needs for this growing population of immigrants and refugees are often unfamiliar, and thus practices to address these challenges are not yet routine for care providers and health care organizations. In particular, complex trauma can make mental health assessments difficult for health care organizations or care providers with limited experience and training in transcultural or trauma-informed care. Using a transcultural approach can improve assessment and screening processes, leading to more effective and high-quality care for immigrant and refugee families experiencing mental health disorders. This paper presents findings from an assessment of current mental health services focusing on current practices and experiences with immigrant and refugee patients and families. The difficulties in developing shared understandings about mental health can hinder the therapeutic process; therefore, it is imperative to ensure an effective assessment right from the beginning, yet there is limited use of existing cultural formulation tools from the DSM-IV or DSM-5. The paper outlines current practices, approaches, challenges, and recommendations shared by mental health care providers and program leaders in addressing the mental health care needs of immigrants and refugees. The results from this study demonstrate that there are many challenges and inconsistencies in providing transcultural, trauma-informed care. Respondents emphasized the need for a thorough yet flexible and adaptive approach that allows for an exploration of differences in cultural interpretations of mental health. Our study concluded that ensuring a mindful, reflexive, transcultural, and trauma-informed health care workforce, and a learning environment to support staff with education, resources, and tools will improve the health care experiences of immigrants and refugees in the mental health care system.